INCOLAB INFORMATION SYSTEM FOR BETTER MANAGEMENT OF ECOSYSTEMS IN THE TRANSBOUNDARY REGION OF THE DANUBE RIVER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article presents the INCOLAB information system for the management of four protected areas for the protection of wild birds included in the European ecological network Natura 2000 in the cross-border region of the Danube River - ROSPA0102 Suhaia and ROSPA0024 Confluence of Olt Danube - Romania, BG0002018 Ostrov Vardim and BG0002070 Ribarnitsi Hadzhi Dimitrovo - Bulgaria. The main purpose of its establishment is to support the control institutions in the decision-making processes and take measures to protect the protected areas and the protected species. The process of creating the system, part of the Joint Bulgarian-Romanian Plan for the Management of the Four Protected Areas for the Protection of Key Bird Species, has been traced, as an innovative model for monitoring and reporting, a new approach for collecting, using and sharing technical, scientific and environmental data. The main functionalities of the information system and the available applications, both for the control authorities and the public, are presented. The visualization of the components of the physical architecture of the information system allows a meaningful structured presentation of the process of building a database with information from different sources. The main benefits of the common information system for the joint management of protected areas and cross-border cooperation are analysed.